(untitled) (Bangladesh Journal of Botany, 2018)
Smoke-water (SW) and biologically active compound butenolide (KAR1) isolated from smoke show stimulating effects on the plant growth of agricultural and horticultural crops, while little has been known on their effects on the secondary metabolism of medicinal plants. Hairy root culture of Salvia miltiorrhiza, an important medicinal plant, was treated with SW and butenolide. The results showed that the contents of salvianolic acid (SAB) and rosmarinic acid (RA) were enhanced with the treatments of SW and KAR1. The expressions of genes (PAL, C4H, 4CL, TAT and HPPR) involved in phenolic acids biosynthesis were upregulated by treatments of SW and KAR1. Responses of C4H and 4CL to SW and KAR1 treatment were later than PAL, TAT and HPPR. It suggests that SW and KAR1have the potential to be used as elicitor to increase the accumulation of secondary metabolites in S. miltiorrhiza hairy root.